A Stability Mathematical Model of Nasopharyngeal Carcinoma on Cellular Level - Sugiyanto Sugiyanto; Fajar Adi Kusumo; Lina Aryati; Mardiah Suci Hardianti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2016)
This paper discussed the stability of “Tumorigenesis Models” to link between EBV and carcinoma of the nasopharyngeal from normal cell to invasive carcinoma. The review on this case accomplished the previous theorem of equilibrium point on “Tumorigenesis Models”.